Determination of thermophysical and desorption properties of elephant foot yam using composition based and fast sorption method. (1st August 2020) - Singh, Punit; Talukdar, Prabal
Highlights: Thermophysical and sorption properties of elephant foot yam are determined. Composition based temperature dependent mathematical models are used for thermophysical properties. Gravimetric and fast sorption methods are used for sorption properties. Abstract: In the present work, thermophysical properties (thermal conductivity, specific heat, density and thermal diffusivity), and sorption properties (water activity and total isosteric heat of desorption) of elephant foot yam (EFY) tuber crop are determined at different temperatures. EFY is a widely consumed tuber crop which is mainly grown in tropical and subtropical regions of Southeast Asian countries. The thermophysical properties are determined using composition and temperature based thermophysical property models for each constituent in conjunction with the constituents present in the food material. Two different methods - gravimetric and fast sorption have been used for determining the sorption properties of EFY. Three sorption models are used to find the best model which describes the experimental sorption behaviour of EFY. It is found that all thermophysical properties increase with temperature except the density of the EFY. The sorption behaviour of EFY is observed as sigmoid shape for all temperatures which comes under II type of sorption isotherm. GAB model is found to be the best model followed by BET and OSWIN model to describe the desorption isotherm of EFY. The total isosteric heat of desorption of EFY drastically increases at lower moisture content as compared to higher moisture content of EFY.